2012
DOI: 10.3389/fpls.2012.00266
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall composition throughout development for the model grass Brachypodium distachyon

Abstract: Temperate perennial grasses are important worldwide as a livestock nutritive energy source and a potential feedstock for lignocellulosic biofuel production. The annual temperate grass Brachypodium distachyon has been championed as a useful model system to facilitate biological research in agriculturally important temperate forage grasses based on phylogenetic relationships. To physically corroborate genetic predictions, we determined the chemical composition profiles of organ-specific cell walls throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 62 publications
9
80
0
Order By: Relevance
“…Histochemical staining of internodes at various developmental stages (data not shown) indicated that lignin deposition increased with progressive maturity, consistent with the biochemical data. The maturation effect on cell wall composition observed in this study is consistent with reports on other grass species [26,27]. Collectively, the data indicate that these biochemical properties vary among stems at different developmental stages (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Histochemical staining of internodes at various developmental stages (data not shown) indicated that lignin deposition increased with progressive maturity, consistent with the biochemical data. The maturation effect on cell wall composition observed in this study is consistent with reports on other grass species [26,27]. Collectively, the data indicate that these biochemical properties vary among stems at different developmental stages (Fig.…”
Section: Resultssupporting
confidence: 92%
“…In B. distachyon, variations in cell wall components (cellulose, hemi-cellulose, and 376 lignin) have been studied in different organs at the seedling, elongating stem and mature stages. For 377 instance, lignin levels are lowest in the leaf and sheath and higher in the stem, with levels increasing as 378 the plant ages (Rancour et al, 2012;Matos et al, 2013). 379…”
mentioning
confidence: 99%
“…Cell wall composition was also examined in Brachypodium distachyon (Rancour et al 2012). Differing from rice, this grass showed more lignin in stem than in leaf blades.…”
Section: Discussionmentioning
confidence: 99%
“…However, saccharification yields of each of these three organs in straws have yet to be extensively analyzed. In addition, the composition of cell walls was also reported to be different between plant developmental stages in Brachypodium (Rancour et al 2012). This suggests that a harvesting stage also affects saccharification yields.…”
mentioning
confidence: 95%
See 1 more Smart Citation